Protection and restriction: A mixed‐methods study of self‐reported well‐being among youth with intellectual disabilities. Issue 1 (19th May 2017) - Boström, Petra; Broberg, Malin
Abstract : Background: As most mental health studies of school‐aged children with intellectual and developmental disabilities (IDD) are based on proxy ratings, the subjective views of these young persons are rarely explored. The present study explores experiences of well‐being, mental ill‐health, family, school, and peer relations in students in special education. Methods: Ten students in special education, aged 13–16 years, answered the Wellbeing in Special Education Questionnaire (WellSEQ) and participated in semi‐structured interviews. Data were analyzed using a mixed methods phenomenological research approach. Results: The general agreement between questionnaire responses and interview accounts appears to be good, and the students emphasized mainly positive emotions and good mental health. Students described their school environment and family relations as inclusive contexts experienced as both protective and restrictive. Conclusion: Using well‐adapted research instruments enables students with IDD to communicate subjective experiences of well‐being and how it relates to aspects of their everyday environment.